Knowledge, attitudes, and diarrhea prevention - Sestiono Mindiharto; Fifit Eka Furi Astutik (Intelektual Pustaka Media Utama, 2019)
The aim of the study was to determine the relationship between knowledge and attitudes in the prevention of diarrheal diseases in patients at the Jaten II Health Center in Karanganyar Regency.This type of correlational analytical research uses a cross sectional approach. The sampling technique in this study is total sampling. The research sample of all members of the population was taken for the study sample, as many as 30 patients suffering from diarrhea. The variables observed were knowledge as an independent variable and attitude in preventing diarrheal disease as the dependent variable. Data analysis employed Chi-square test.The results showed that knowledge of diarrheal diseases in the majority of patients was quite as many as 16 respondents or 53.3%. The attitude in the prevention of diarrheal diseases in the majority of patients was less than 16 respondents or 53.3%. There is a significant relationship between knowledge and attitudes in the prevention of diarrheal disease in patients at the Jaten II Health Center in Karanganyar Regency with a value of p = 0.012.It is suggested that the prevention of diarrheal diseases is highly needed by high patient awareness to get a clean and healthy life.